Company Event Manager - Pavļenko, Maksims (Latvijas Universitāte, 2019)
Sekojošais dokuments ir noslēguma darbs programminženierijas kursā. Darba autori:Maksims Pavļenko. Dokuments ir programmatūras prasību specifikācija produktam „Company Event Manager”, kura mērķis ir lielo uzņēmumu darbinieku profesionālo prasmju uzlabošana, sniedzot informāciju par attīstības iespējām, kā arī palīdzētu orientēties ziņu plūsmā, laika plānošanai pašrealizācijai un uzlabot komandas darbu uzņēmumā.

The following document is the final work of the programme engineering course. The authors of the work: Maksims Pavlenko. The document is a specification of the software requirements for the “Company Event Manager”, which aims to improve the professional skills of employees of large companies by providing information on development opportunities, as well as helping you to orient yourself in the news flow and time planning for self-realization and to improve teamwork in the company.
Company Event Manager
Keywords: Datorzinātne; izglītība; komandas darbs; pasākumi; education; teamwork